ESG Performance, Outside Directors, dan Firm Performance: Sebuah Analisis Empiris - Candy; Tan, Ie Ling; Yopie, Santi (Universitas Pamulang, 2025)
The concept of Environmental, Social, and Governance (ESG) has gained significant momentum in the global business landscape, including in Indonesia. However, the effectiveness of ESG implementation on firm performance has rarely been examined from the perspective of internal governance mechanisms, particularly the role of outside directors. This study analyzes the effect of ESG performance on firm performance, considering outside directors as a mediating variable. A quantitative approach was applied using purposive sampling on 84 companies that have adopted ESG principles. Secondary data were analyzed using Stata software. The regression results indicate that ESG performance has a positive and significant effect on return on assets (ROA) but no significant effect on return on equity (ROE). Outside directors have a negative effect on ROA and do not significantly mediate the relationship between ESG performance and ROE. The mediation effect is competitive, meaning that outside directors reduce the positive influence of ESG performance on ROA. These findings underscore the need to re-evaluate the structure and capacity of outside directors in supporting corporate sustainability strategies.